2000
DOI: 10.1046/j.1365-2486.2000.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence that symbiotic N2 fixation in fertile grassland is an important trait for a strong response of plants to elevated atmospheric CO2

Abstract: Summary Although legumes showed a clearly superior yield response to elevated atmospheric pCO2 compared to nonlegumes in a variety of field experiments, the extent to which this is due to symbiotic N2 fixation per se has yet to be determined. Thus, effectively and ineffectively nodulating lucerne (Medicago sativa L.) plants with a very similar genetic background were grown in competition with each other on fertile soil in the Swiss FACE experiment in order to monitor their CO2 response. Under elevated atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 40 publications
2
68
1
Order By: Relevance
“…Reich et al, 2001;Lee et al, 2003;Ainsworth and Long, 2005). Furthermore, experiments comparing nodulating and nonnodulating genotypes within a legume species have found that N fixers are more responsive to elevated [CO 2 ] than nonfixers (Nakamura et al, 1999;Luscher et al, 2000;Ainsworth et al, 2002Ainsworth et al, , 2004. However, there is also significant variation in the magnitude of the response to elevated [CO 2 ] among legume species and genotypes (Reich et al, 2001;West et al, 2005), and legume aboveground primary production was not statistically greater than that of other functional types when averaged across four Free Air CO 2 Enrichment (FACE) experiments (Nowak et al, 2004).…”
Section: Are Legumes More Responsive To Elevated [Co 2 ] Than Other Pmentioning
confidence: 99%
“…Reich et al, 2001;Lee et al, 2003;Ainsworth and Long, 2005). Furthermore, experiments comparing nodulating and nonnodulating genotypes within a legume species have found that N fixers are more responsive to elevated [CO 2 ] than nonfixers (Nakamura et al, 1999;Luscher et al, 2000;Ainsworth et al, 2002Ainsworth et al, , 2004. However, there is also significant variation in the magnitude of the response to elevated [CO 2 ] among legume species and genotypes (Reich et al, 2001;West et al, 2005), and legume aboveground primary production was not statistically greater than that of other functional types when averaged across four Free Air CO 2 Enrichment (FACE) experiments (Nowak et al, 2004).…”
Section: Are Legumes More Responsive To Elevated [Co 2 ] Than Other Pmentioning
confidence: 99%
“…2, Table 2). Other legumes also increased A at elevated CO 2 due to increased nodule activity at elevated CO 2 (Hungate et al 1999;Lüscher et al 2000). Increase in A observed in non-legumes was due to the increased root size and/or root activity by elevated CO 2 .…”
Section: Discussionmentioning
confidence: 85%
“…Nakamura et al (1999) observed that plant dry mass increased at elevated CO 2 in a nodulated soybean (Glycine max) but did not in the non-nodulated isogenic line. Similarly, dry mass and N per plant increased at elevated CO 2 in nodulated lucerne (Medicago sativa) while they did not in a less-nodulated isogenic line (Lüscher et al 2000). Ainsworth et al (2004) found that the lightsaturated rate of leaf photosynthesis was stimulated by elevated CO 2 in a nodulated cultivar of soybean but was not in the non-nodulated isogenic line.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller yield reductions could potentially be counterbalanced in the future by the fact that forage legumes react particularly strongly and positively to the CO 2 fertilisation effect, through higher rates of photosynthesis, more efficient use of water, and increased rates of N 2 -fixation (Lüscher et al 2000, Zanetti et al 1996, Kimball et al 2002. However, the positive consequences of the CO 2 fertilisation effect are limited to conditions without water shortages or nutrient deficiencies (Rogers et al 2009;Hopkins and Del Prado 2007), but in the future both of these factors will more frequently affect LGS on organic farms in Brandenburg.…”
Section: Discussionmentioning
confidence: 99%